2000
DOI: 10.1027//0227-5910.21.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Child and Adolescent Suicide Deaths in New Mexico, 1990-1994

Abstract: The suicide death rate in New Mexico is consistently higher than the national rate. Among adolescents, suicide is the third leading cause of death nationally, but in New Mexico it is the second leading cause of death. This study describes the pattern of adolescent suicide deaths in New Mexico. We conducted a retrospective review of all medical examiner autopsies for adolescent suicides (ages 20 years and younger) in New Mexico from 1990-1994. Records were reviewed for demographics and possible contributing fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…A combination of these two methods in planned complex suicide seems to be very rare, and has not been described until very recently [8,9]. The first method employed, namely the use of firearms, is frequently used in cases of suicide [10,11]. The use of firearms has earlier been described as one of the most preferred methods employed in planned complex suicide, and is, in most cases, employed by men [2,4,7,12].…”
Section: Discussionmentioning
confidence: 98%
“…A combination of these two methods in planned complex suicide seems to be very rare, and has not been described until very recently [8,9]. The first method employed, namely the use of firearms, is frequently used in cases of suicide [10,11]. The use of firearms has earlier been described as one of the most preferred methods employed in planned complex suicide, and is, in most cases, employed by men [2,4,7,12].…”
Section: Discussionmentioning
confidence: 98%
“…Alcohol and other drugs were reported in 74% of Native American adolescent suicides, yet only 55% of Hispanic and 37% of non-Hispanic Caucasian suicides during the same period (Werenko et al, 2000).…”
Section: American Indian/alaska Native Suicidementioning
confidence: 98%
“…Werenko et al (2000) found that 18% of the 184 youth they studied had a history of substance abuse, and that 50% had drugs or alcohol present at the time of death by suicide. Additional evidence comes from a study by Renaud, Brent, Birmaher, Chiappetta, & Bridge (1999), in which 1/3 of those who died by suicide had a positive toxicology screen for substances.…”
Section: Background and Significancementioning
confidence: 99%
“…Werenko et al (2000) found evidence of family dysfunction among 33% of the 186 young people who died by suicide in New Mexico between 1990 and 1994. King et al (2001) found a significant association between suicide ideation or attempts and stressful life events, poor family environment, and low parental monitoring, among other factors, in a community sample of 1285 individuals ages 9–17 years.…”
Section: Background and Significancementioning
confidence: 99%
See 1 more Smart Citation